The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1159/000052086
|View full text |Cite
|
Sign up to set email alerts
|

Thiamine-Responsive Acute Neurological Disorders in Nonalcoholic Patients

Abstract: Wernicke’s encephalopathy (WE) is most commonly associated with alcoholism, although other causes have also been implicated. In the years 1994–1997, 9 patients with no history of alcohol abuse presented with acute signs of ophthalmoplegia or nystagmus and ataxia which resolved within 48 h after intravenous thiamine. There were 7 women and 2 men aged 17–57 (7 below the age of 30). Precipitating events included vomiting 2, drastic weight-reducing diet 2, renal colic in a postpartum woman 1, colonic surgery 2 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 11 publications
0
15
0
2
Order By: Relevance
“…Recent case studies reveal vulnerability in patients with thiamine deficiency secondary to anorexia nervosa or other psychiatric conditions, prolonged intravenous feeding without proper supplementation, gastrointestinal surgery (especially bariatric surgery), and systemic malignancy. [34] Thiamine is a cofactor for several key enzymes important in energy metabolism, including transketolase, alpha-ketoglutarate dehydrogenase, and pyruvate dehydrogenase. Thiamine requirements depend on metabolic rate, with the greatest need during periods of high metabolic demand and high glucose intake (including glucose-containing intravenous fluids).…”
Section: Discussionmentioning
confidence: 99%
“…Recent case studies reveal vulnerability in patients with thiamine deficiency secondary to anorexia nervosa or other psychiatric conditions, prolonged intravenous feeding without proper supplementation, gastrointestinal surgery (especially bariatric surgery), and systemic malignancy. [34] Thiamine is a cofactor for several key enzymes important in energy metabolism, including transketolase, alpha-ketoglutarate dehydrogenase, and pyruvate dehydrogenase. Thiamine requirements depend on metabolic rate, with the greatest need during periods of high metabolic demand and high glucose intake (including glucose-containing intravenous fluids).…”
Section: Discussionmentioning
confidence: 99%
“…Increased thiamine consumption due to the rapid growth of cancer cells and inadequate nutrition due to nausea and anorexia from chemotherapy or malabsorption syndrome have been suggested as possible reasons for cancer-associated WE 6 7…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggested that thiamine might have a role in dopaminergic neuron activity. Interestingly, parental thiamine administration was used successfully in 9 non-alcoholic patients who presented with acute neurological disorders [108]. Administration of the combination of thiamine and acetazolamide was reported to reduce scores on the Abnormal Involuntary Movement Scale (AIMS) and the Simpson-Angus Neurological Rating Scale (ANRS) in patients with the tardive dyskinesia and parkinsonism symptoms [109].…”
Section: Non-genomic Role Of Thiamine In Parkinson's Diseasementioning
confidence: 99%